Pattern of cannabis and cigarette abuse among adolescent students in Sokoto and assessment of antinutritional components of the two drugs - Yusuf Yahaya Miya; Rose Livinus; Umar AI; Yusuf Sarkingobir; Murma Thomas Butuwo; Zayyanu Bello (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
This study aimed to determine the pattern of cannabis and tobacco use among adolescent students in Sokoto and measure antinutritional factors in the two drugs. Qualitative and quantitative standard methods were applied. Reagents and materials of analytical grade were used to evaluate the antinutrients. Signs of drug abuse among adolescents are untidiness (33.3%), blackening of lips and toes (24.2%), poor concentration (20.0%), poor/foul odor (12.1%), false images (6.7%), hostility (5.5%), and reduced weight (1.2%). The perceived causes of drug abuse are peer pressure (36.4%), poor parental guidance (30.3%), labor/work (15.2%), learning musical art (9.1%), unemployment (6.1%), and sports (3.0%). The submitted effects linked to cannabis and cigarette revealed are health effects (27.3%), followed by poor academic performance (24.2%), confusion (21.2%), school dropout (16.9%), disrespect (7.3%), and lastly disrespect (3.0%). The preventions are strict restriction on drugs (33.3%), education/awareness about the effects of drug abuse (26.7%), religious intervention (21.2%), avoiding deviant peers (9.7%), and poor parental guidance (9.1%). Substance abuse is a menace among the studied adolescents, and antinutrients present in the drugs affect the users, especially their academic performance. Penelitian ini bertujuan untuk mengetahui pola penggunaan ganja dan tembakau di kalangan pelajar remaja di Sokoto dan mengukur faktor antigizi pada kedua obat tersebut. Metode standar kualitatif dan kuantitatif digunakan dalam penelitian ini. Reagen dan bahan kelas analitik digunakan untuk mengevaluasi antinutrien. Tanda-tanda penyalahgunaan narkoba di kalangan remaja adalah penampilan acak-acakan (33,3%), bibir dan jari kaki menghitam (24,2%), kurang konsentrasi (20,0%), tidak sedap/bau busuk (12,1%), citra palsu (6,7%), membuat keributan (5,5%), dan penurunan berat badan (1,2%). Penyebab penyalahgunaan narkoba yang dirasakan adalah tekanan dari teman sebaya (36,4%), bimbingan orang tua yang buruk (30,3%), buruh/bekerja (15,2%), belajar seni musik di tempat yang kurang baik (9,1%), pengangguran (6,1%), dan olahraga (3,0%). Efek yang diajukan terkait dengan ganja dan rokok yang terungkap adalah efek kesehatan (27,3%), prestasi akademik yang buruk (24,2%), kebingungan pada tujuan hidup (21,2%), putus sekolah (16,9%), tidak peka (7,3%), dan terakhir rasa hormat rendah (3,0%). Salah satu upaya pencegahannya yaitu pembatasan narkoba yang Ketat (33,3%), pendidikan/kesadaran tentang dampak penyalahgunaan narkoba (26,7%), intervensi agama (21,2%), menghindari pergaulan yang menyimpang (9,7%), dan bimbingan orang tua (9,1%). Penyalahgunaan zat merupakan ancaman di kalangan remaja yang diteliti dan antinutrien yang terkandung dalam obat-obatan tersebut mempengaruhi penggunanya, terutama prestasi akademis.